Effectiveness of Educational Program Based on the Theory of Reasoned Action to Decrease the Rate of Cesarean Delivery Among Pregnant Women in Fasa, Southern Iran - Ali Khan-Jeihooni; Fatemeh Shahidi; Seyed Mansour Kashfi (Hamadan University of Medical Sciences, 2014)
Introduction: Cesarean section is considered as a major surgery accompanied by several complications. The present study aimed to determine the effect of educational intervention based on the theory of reasoned action to reduce the rate of cesarean section among pregnant women in Fasa, Southern Iran. Materials and Methods: This quasi-experimental study was performed on 100 (50 participants in each of the control and intervention groups) primiparous women in the third trimester of pregnancy admitted to health centers of Fasa city, Fars province, Iran. The data-gathering tool was a multipart questionnaire containing demographic variables and the theory of reasoned action structures. After the pretest, the intervention group underwent exclusive training based on the theory of reasoned action. Then, after 3 months, both groups took part in the posttest. Data was analyzed by paired T-test, independent T-test and chi-square using SPSS-18 software. Results: A significant difference was found between the two groups regarding knowledge, evaluations behavioral outcomes, Behavioral beliefs and intention (P<0.001). Chi-square analysis showed a significant difference between the two groups regarding their performance (P<0.001). Conclusion: The present intervention was effective in increasing the pregnant women's knowledge, evaluation of outcomes, attitude and strengthening their intention as well as performance. Therefore, it is suggested to use this model and other systematic straining for pregnant women to decrease the rate of cesarean section.